Pengaruh Persepsi Siswa Tentang Metode Mengajar Guru dan Kemandirian Belajar Terhadap Hasil Belajar Akuntansi Pada Siswa Kelas X Akuntansi SMK PGRI 3 Kediri - Zuliana Sari, Kiky; Yusuf Afandi, Tjetjep; Surindra, Bayu (Universitas Nusantara PGRI Kediri, 2021)
Abstract Basically students have a positive assumption on the way that the subject teacher uses the way in teaching and delivering materials. Based on the results of the initial research at SMK PGRI 3 Kediri, it is known that the value obtained by students is less than the maximum. Where the learning results obtained by students are still below the minimum completion criteria (KKM) of seventy-five (75). This research aims to know the influence between teacher methods in teaching and the level of independence in students' learning, as well as changes in student learning outcomes in accounting subjects at SMK PGRI 3 Kediri. The research method used in this study is quantitative method with double regression approach. Where the object is a grade X student of 25 students. The results of this study generally showed a positive influence or have a significant influence on the methods and ways used by teachers in teaching, as well as the influence between the independence carried out by students during learning on the results obtained by students in learning in school. Furthermore, students' perception of the methods used by teachers in teaching and showing self-reliance in learning, simultaneously has a positive and significant influence. Keywords: Teacher Teaching Method, Self-Reliance, Learning Outcomes